Measuring the Productivity of the Foods and Beverages Industries in Indonesia: What Factors Matter? - Mohammad Zeqi Yasin (Economics and Finance in Indonesia, 2021)
The foods and beverages industries have shown the largest share of output in the manufacturing sector of Indonesia for more than a decade. This study aims to investigate its performance indicators through the  growth of total factor productivity (TFP) and its determinants, such as imported raw materials, exports, absorptive capacity, firm size, market concentration, and capital ownership. This study employed firm-level panel data from 2008–2015 and the Growth Accounting method of Solow residual in addition to the fixed effects model to estimate TFP growth and its determinants. The results show that the foods and beverages industries in Indonesia showed positive TFP growth from 2008–2015. Moreover, variables of absorptive capacity, firm size, and market concentration promote the TFP growth of firms. Meanwhile, import intensity discourages TFP growth. However, within a certain threshold, firms with import activities perform better than non-importer firms. However, imports and exports may entail transfer of technology and knowledge and will be the bridge between the firms and the advanced market. This study recommends that policy makers increase the managerial capabilities of firms through a more massive training program as well as provide incentives to workers in the form of rewards or relief of income tax, while also improve product competitiveness through more intensive programs on the Indonesian National Standard (SNI) and the Domestic Component Level (TKDN).